PENGARUH KEMAMPUAN TEKNIK PERSONAL, KECANGGIHAN TI DAN DUKUNGAN MANAJEMEN PUNCAK TERHADAP EFEKTIVITAS SIA PADA KRISNA OLEH-OLEH KHAS BALI III - Cahyani, Luh Nyoman Pradnya; Putra, I Made Pande Dwiana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
The effectiveness of an accounting information system is one of the important foundations that assist workers in producing timely, accurate, and reliable reports for the decision-making process of a company. This study aims to determine the effect of personal technical skills, IT sophistication and top management support on the effectiveness of AIS. This research was conducted at Krisna Souvenirs Typical Bali III using a quantitative approach. The sample was determined by purposive sampling technique and obtained a sample of 35 people. The data collection method used in this research is a questionnaire distributed directly to employees and the data analysis technique used is multiple linear regression analysis which is processed with the help of SPSS. The results showed that the ability of personal techniques and top management support had a positive and significant effect on the effectiveness of AIS, while IT sophistication had a negative effect on the effectiveness of AIS at Krisna By-Oleh Khas Bali III, this could happen because the system was sophisticated and not followed by the user's proficiency in operate the system and there is no user involvement during the system development process so that the advantages and disadvantages of the system have not been detected accurately.